The Impact of Centralization and Decentralization Policies on Teacher Performance at the Hidayatullah Educational Institution in Balikpapan - Rizqa Anisa Hillan; Karoso, Subianto; Handayani, Enie Wahyuning; Yanuartuti, Setyo; Pujosusanto, Ari (Journal of Practice Learning and Educational Development, 2024)
This study aims to analyze the impact of centralization and decentralization policies on teacher performance at the Hidayatullah Education Institution in Balikpapan. Using a quantitative approach, the research employs questionnaires, interviews, and observations as data collection methods. The findings indicate that centralization policies help maintain consistency in curriculum standards and evaluation, while decentralization policies enhance creativity and innovation in teaching. However, coordination between these two policies remains a challenge. With a balanced strategy, the combination of centralization and decentralization policies can improve teacher performance and the quality of education. This study offers practical and theoretical contributions to the development of more adaptive educational policies.